Maternal Health, Child Health and Nutrition in Lao PDR : Evidence from a Household Survey in Six Central and Southern Provinces - World Bank (Washington, DC, 2014)
Despite being on-track on the child- and maternal-health Millennium Development Goals (MDGs), Lao PDR continues to have some of the worst maternal and child health (MCH) and nutrition outcome indicators, both globally as well as in the East Asia and Pacific (EAP) region. This report presents results from a household, village, and facility survey on Maternal and Child Health (MCH) and nutrition in mostly rural areas of six central and southern provinces of Lao People's Democratic Republic (PDR). The information in this report localizes MCH and nutrition-related information that are typical for sampled catchment areas of selected health centers in six central and southern provinces of the country. In addition, the report summarizes data on service availability and readiness of health centers in terms of their ability to provide key MCH & nutrition-related services. The results from this survey thus shed light on what it would take to attain the health-related MDGs. In order to improve the level and equity of maternal and child health indicators, interventions would need to address numerous demand-side barriers, including physical access barriers, financial barriers, and cultural, linguistic, and educational barriers.